Human Settlements Along Bago River: Their Socio-Economic Conditions and Activities - Menes, Carmen C.; Lacson, Clarita T.; Alvarez, Raul C.; Dales, Alma P.; Linaugo, Joji D. (Silliman Journal, 2022)
Human settlements in four purposely chosen sections of Bago 3JWFS XFSF TVSWFZFE VTJOH RVFTUJPOOBJSFT TVQQMFNFOUFE XJUI GPDVT HSPVQ EJTDVTTJPOT 5IF FDPOPNJD CFOFmUT EFSJWFE GSPN the utilization of the river were given emphasis. Semi-permanent (45.49%) and lightly built houses (27.08%) in riverine communities are located in areas almost proximate to the easement. Fishing (81 or 29.24%) is a critically important occupation or source of income. The residents are highly dependent on the river for food, primarily mTI BOEDSVTUBDFBOT 3JDF DPSO WFHFUBCMFT bananas, and root crops are cultivated by the local inhabitants along the river bank. A notably high number of households utilize river water for domestic uses (53.07% for laundry; 49.46% for bathing). Almost 60% of the respondents do not have toilets and dispose their FYDSFUBJOTVHBSDBOFQMBOUBUJPOT DPSOBOE SJDFmFMET PO SJWFS banks, and in the river itself while their garbage is dumped in open areas. The high (2,200 - >16,000,000 MPN/100 ml) coliform readings in all stations can be attributed to use of the river as dumping site of human, animal and agricultural wastes. The coliform analysis showed that there was fecal contamination of the river and that the water is therefore not safe for drinking.